Primers for phylogeny reconstruction in Bignonieae (Bignoniaceae) using herbarium samples(1) - Zuntini, Alexandre R. (Botanical Society of America, 2013)
• Premise of the study: New primers were developed for Bignonieae to enable phylogenetic studies within this clade using herbarium samples. • Methods and Results: Internal primers were designed based on available sequences of the plastid ndhF gene and the rpl32-trnL intergenic spacer region, and the nuclear gene PepC. The resulting primers were used to amplify DNA extracted from herbarium materials. High-quality data were obtained from herbarium samples up to 53 yr old. • Conclusions: The standardized methodology allows the inclusion of herbarium materials as alternative sources of DNA for phylogenetic studies in Bignonieae.